Hungarian Monitoring, 3 August 1988 . [Magyar rádiófigyelő], 1988. augusztus 3 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Mathias Rust's release - Polish domestic situation Domestic Affairs: - Károly Grósz evaluates his American trip at press conference - Vienna-Budapest World Exposition - Access to telephone lines - Housing availability - Szeged Open Air Games: Csíksomlyó Passion Economy: - Tourism income and losses - National Association of Entrepreneurs (VOSZ) protests against 50% tax on profits - The chemical industry Külpolitika: - Matthias Rust szabadon bocsátása - Lengyel belpolitikai helyzet Belpolitika: - Grósz Károly sajtóértekezleten értékeli amerikai útját - Bécs-Budapest Világkiállítás - Telefonvonalhoz jutás helyzete - Lakáshoz jutás helyzete - Szegedi Szabadtéri Játékok: Csíksomlyói passió Gazdaság: - Idegenforgalmi bevételek és veszteségek - A VOSZ tiltakozik az 50%-os nyereségadó ellen - Vegyipar